The National Food Security Act (NFSA) 2013: Challenges, buffer stocking and the way forward - Shweta Saini; Ashok Gulati (Indian Council for Research on International Economic Relations (ICRIER), 2015)
The National Food Security Act (NFSA) 2013 combines and expands the scope of some existing food-based welfare schemes. It will be distributing raw rations, meal(s) and/or cash. Approximately 81.35 crore persons or 16.57 crore households are to benefit under the targeted public distribution system (TPDS) under the Act. The annual food grain requirement is estimated at 61.43 million tonnes with annual food subsidy implication of around Rs. 1.31 lakh crore. The paper empirically maps the annual distribution commitment (61.43 MMTs) of the government with the procurement pattern of rice and wheat, for each quarter, to estimate the quarterly operational stocking norms. In addition to the 61.4 MMTs grains, needed to meet the operational needs, the country also stocks for strategic needs. The paper proposes creation of 10 MMTs of grains in this regard- five MMTs to be procured from the domestic market and the remainder from the international market on a need basis. By re-introducing the concept of fungibility between the operational and strategic stocks and by utilizing the dynamics of the procurement pattern, the paper shows that the 61.4 MMTs of annual grain procurement will be sufficient for both the operational and strategic stock needs of the country. The estimated new norms (Scenario 2) are January - 21 MMTs, April - 18.7 MMTs, July - 36.8 MMTs and October - 24 MMTs. Recently approved CCEA norms, on comparison, are found to be on the higher side indicating the government's implicit preference for lower risk (the government stocks higher levels of strategic reserves, used mainly to smoothen inter/intra year fluctuations, than required) even if that implies higher costs. There are wider apprehensions that the Act will fail to deliver on the promises made. The bigger operational challenges include- ensuring the adequate supply of grains every year, lowering per person entitlement or population coverage particularly when the population is expanding, unpreparedness of the implementing states, slowing down the natural process of agricultural diversification by increasing the relevance of rice and wheat in the system. Therefore, the immediate suggestion is not to hurry in the NFSA implementation process, especially not without satisfying its pre-conditions in each state. Explicit challenges that the continuation of the existing system pose on the system warrants one to devise an appropriate income policy instrument to substitute NFSA (...)
Keywords: Q18; I38; H42; E61; 330; Buffer stock; India; agriculture; National Food Security Act (NFSA); FCI; Cash Transfers